A review of instruments to measure interprofessional collaboration for chronic disease management for community-living older adults. Issue 2 (3rd March 2016) - Bookey-Bassett, Sue; Markle-Reid, Maureen; McKey, Colleen; Akhtar-Danesh, Noori
ABSTRACT: It is acknowledged internationally that chronic disease management (CDM) for community-living older adults (CLOA) is an increasingly complex process. CDM for older adults, who are often living with multiple chronic conditions, requires coordination of various health and social services. Coordination is enabled through interprofessional collaboration (IPC) among individual providers, community organizations, and health sectors. Measuring IPC is complicated given there are multiple conceptualisations and measures of IPC. A literature review of several healthcare, psychological, and social science electronic databases was conducted to locate instruments that measure IPC at the team level and have published evidence of their reliability and validity. Five instruments met the criteria and were critically reviewed to determine their strengths and limitations as they relate to CDM for CLOA. A comparison of the characteristics, psychometric properties, and overall concordance of each instrument with salient attributes of IPC found the Collaborative Practice Assessment Tool to be the most appropriate instrument for measuring IPC for CDM in CLOA.